Comparative Analysis of Clustering using AODV DSDV and CBRP - Kaur, Arshdeep; Kumar Arora, Sandeep; Masud, Mahedi (International Journal of Engineering and Technology, 2018)
In a network whether wireless or wired, a set of protocols which are used to distribute the information through various routes between the nodes are said to be the routing protocols which serves as a majorly vital part of the computer networks. They specify the particular and specific path of information exchange by the sending and receiving of packets. Vehicular ad- hoc networks are quite emerging technologies of todayâ€™s era presenting the provision of seamless and uninterrupted communication in the network of mobile nodes in dynamic environment. Routing itself proves to be quite a considerable and crucial challenge where the routing protocol named AODV performs its best by proving itself considerably more efficient. The stated paper focuses on the Performance comparison of the conventional protocols AODV and DSDV where AODV outperforms DSDV and offers better QoS but such conventional protocol proves to be inauspicious in VANET. This paper gives verification of better QoS of cluster based routing protocol CBR over the conventional routing protocols. The Simulation and comparison results have been carried out in Network Simulator NS-2 to briefly elaborate the impact of AODV DSDV and CBR routing protocols on the bases of Throughput, Normalized Routing Load, Control overheads, delay, Jitter and Packet drop ratio as performance metrics.Â Â